Hearing Loss Among World Trade Center Firefighters and Emergency Medical Service Workers. Issue 12 (December 2019) - Flamme, Gregory A.; Goldfarb, David G.; Zeig-Owens, Rachel; Hall, Charles B.; Vaeth, Brandon M.; Schwartz, Theresa; Yip, Jennifer; Vossbrinck, Madeline; Stein, Cheryl R.; Friedman, Liza; Cone, James E.; Prezant, David J.
Abstract : Objective: To determine if World Trade Center (WTC) exposure is associated with hearing loss. Methods: Logistic regression to evaluate the immediate impact of WTC exposure and parametric survival analysis to assess longitudinal outcomes. Results: Those arriving on the morning of September 11, 2001 had elevated odds of low-frequency (odds ratio [OR]: 1.24; 95% confidence interval [CI]: 1.04 to 1.47) and high-frequency (OR: 1.16; 95% CI: 1.02 to 1.31) hearing loss at their first post-September 11, 2001 examination. Longitudinally, participants arriving before September 13, 2001 and spending more than or equal to 6 months at the WTC-site had greater risk of hearing loss in the low frequencies (risk ratio [RR]: 1.31; 95% CI: 1.05 to 1.60) and high frequencies (RR: 1.37; 95% CI: 1.22 to 1.54). By 2016, 3194 (37%) had abnormal hearing sensitivity in either ear and 1751 (20%) in both ears. Conclusions: More heavily WTC-exposed workers were at increased risk of hearing loss, and group differences persisted for at least 15 years. Those with abnormal hearing sensitivity may benefit from interventions such as hearing aids and other rehabilitation.